2022
DOI: 10.2174/18743501-v15-e2206090
|View full text |Cite
|
Sign up to set email alerts
|

Online Deceptive Impression Management: Self-admission and Other Estimates of False Facebook-selves

Abstract: Background: People deceive online. There is, however, mixed evidence about whether people present themselves falsely on Facebook. We investigated to what extent people present their true selves on Facebook. As generally, people estimate their own behavior as ‘less evil’ than the behaviors of others, we also assessed people’s estimations of whether other people present their true selves on Facebook. Methods: In two studies (n=94, n=189), participants filled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…As the variety of online personas received by students' increases, students are influenced by them. Some studies have shown that they enjoy deceptive image management on public social platforms [7]. Existing research has found that social media has a two-sided impact on users: on the one hand, it enriches interactions, promotes self-presentation, maintains relationships and makes information more accessible; but at the same time, it also induces negative emotions such as anxiety, depression, jealousy, social fatigue and even unethical behavior [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As the variety of online personas received by students' increases, students are influenced by them. Some studies have shown that they enjoy deceptive image management on public social platforms [7]. Existing research has found that social media has a two-sided impact on users: on the one hand, it enriches interactions, promotes self-presentation, maintains relationships and makes information more accessible; but at the same time, it also induces negative emotions such as anxiety, depression, jealousy, social fatigue and even unethical behavior [8,9].…”
Section: Introductionmentioning
confidence: 99%